SISTEM PENDUKUNG KEPUTUSAN KENAIKAN PANGKAT KARYAWAN PERSEROAN TERBATAS PELAYARAN KUMAFA LAGUN MARINA BENGKULU - Asnawati, Asnawati; Kanedi, Indra (UNIVED Press, 2012)
This study aims to create a Decision Support System applications increase rank by using Visual Basic 6.0 programming language, in order to facilitate Kumafa Shipping Company Limited Lagun Marina to get employees to be promoted, as well as simplify management determines appropriate employees increased rank.Data collection methods used in this thesis pembutan the method of observation and literature. From the results of research by the author, it can be concluded that the application of Decision Support Systems pembutan Increase Employees Rank Company Limited Lagun Marina Kumafa using the programming language Visual Basic 6.0 and Microsoft Office Access 2003. Can improve the quality of the Limited Liability Kumafa Lagun Marina Bengkulu in Decision Making Increase Rank.